Synthesis, characterization and electrochemical sensors application of MnO2 nanoparticles. (2022) - Shoba, A.; Kavitha, B.; Aswathaman, H.; Ganesan, H.; Senthil Kumar, N.
Abstract: The prepared MnO2 nanoparticles were characterized through electronic spectroscopy. The band gap value of nanoparticles is 3.12 eV. The stretching vibration band of nanoparticles of MnO2 at 631 cm −1 can be assigned to Mn–O. The manganese oxide nano flower–like structure, proved through atomic force microscopy (AFM) photographic studies. The MnO2 morphology was confirmed uniform coating on the electrode surface. Glassy carbon electrode (GCE) was modified with manganese oxide nanoparticles to enhance the electrocatalytic activity of the redox behavior of ascorbic acid. The oxide nano flower modified electrode is used as fresh voltammetric determination of ascorbic acid. The results of voltammetric behavior are satisfactory in the electro oxidation of ascorbic acid, and exhibit considerable improvement compared to glassy carbon electrode. Under the optimized experimental conditions, the modified electrode exhibit better linear dynamic range from 50 μg/L to 500 μg/L with lower limit of detection 30 μg/L for the stripping voltammetric determination of ascorbic acid. The real sample solution of ascorbic acid was successfully applied for accurate determination of trace amounts on nanomaterials modified electrode.